2006
DOI: 10.1080/08880010600692526
|View full text |Cite
|
Sign up to set email alerts
|

CHILDHOOD CANCER: Its Impact and Financial Costs for Australian Families

Abstract: This study evaluated the impact and financial costs of childhood cancer for Australian families by means of a nonrandomized retrospective cross-sectional survey at the oncology department of a large metropolitan pediatric hospital. The Family Impact Scale (a standardized questionnaire) and the self-reported economic burden (a questionnaire on expenses and lifestyle changes) were utilized. Results of the family impact score were compared to a previously published cohort of children with insulin-dependent diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
109
2
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(126 citation statements)
references
References 10 publications
9
109
2
4
Order By: Relevance
“…The existing studies are relatively small and are likely to reflect policies and labor markets in particular geographic areas (10;28-35), and only a few utilizes a comparison group (29)(30)(31). Overall, the results from Norway are more positive and suggest lesser declines in earnings than what has been reported previously (10;28;31;33;35), perhaps due to Norway's extensive welfare system.…”
Section: Employment and Earningscontrasting
confidence: 52%
“…The existing studies are relatively small and are likely to reflect policies and labor markets in particular geographic areas (10;28-35), and only a few utilizes a comparison group (29)(30)(31). Overall, the results from Norway are more positive and suggest lesser declines in earnings than what has been reported previously (10;28;31;33;35), perhaps due to Norway's extensive welfare system.…”
Section: Employment and Earningscontrasting
confidence: 52%
“…Major challenges regarding access to diagnostic, treatment, and support services invariably confront cancer patients who come from these isolated areas (26)(27)(28). This may mean extended periods away from home for all or part of the family while medical care for a child with cancer is being sought, causing financial strain as well as the disruption of normal family and social routines (29,30). Such difficulties could in turn have a bearing on survival to an extent that might not be evident in geographic studies within other countries.…”
Section: Discussionmentioning
confidence: 99%
“…These high costs are concerning due to most Pacific countries falling into the low to middle income country categories. The Journal of Paediatric Hematology found that the burden of cancer treatment costs were centered on out of pocket payments, such as travel, communication and accommodation [24].…”
Section: Discussionmentioning
confidence: 99%